Instrument choice and personality - Pitkänen, Petro (2022)
The process of how people choose which musical instrument to play is complex. This study aimed at seeing how personality affects the decision-making process and if there were any differences in personality between players of different instrument groups. The relationship between personality type and the reasons behind instrument choice was explored in this study, to provide insights into how personality potentially influences the instrument a musician chooses to play. The study was conducted through an online questionnaire directed at music students in secondary or tertiary levels of the Finnish education system. The study had 329 respondents ranging from 18 to 30 years of age from across Finland. The Big Five inventory was used to measure how respondents scored on each of the five personality dimensions and the data was analysed using quantitative measures. The results suggest that personality does have some effect on how people choose their instruments, though it is not the sole, driving force behind instrument choice. The most significant findings arose when comparing groups of different instrumentalists and their reasons for playing their instrument of choice. The results suggest that instruments are chosen by other, more practical means, rather than by personality. These results give room for future research into how personality affects our life choices, as well as what music teachers can gain from understanding this phenomenon.